2021
DOI: 10.3390/cells10010186
|View full text |Cite
|
Sign up to set email alerts
|

ICU Admission Levels of Endothelial Biomarkers as Predictors of Mortality in Critically Ill COVID-19 Patients

Abstract: Endotheliopathy is suggested to be an important feature of COVID-19 in hospitalized patients. To determine whether endotheliopathy is involved in COVID-19-associated mortality, markers of endothelial damage were assessed in critically ill COVID-19 patients upon intensive care unit (ICU) admission. Thirty-eight critically ill COVID-19 patients were included in this observational study, 10 of whom died in the ICU. Endothelial biomarkers, including soluble (s)E-selectin, sP-selectin, angiopoietin 1 and 2 (Ang-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(141 citation statements)
references
References 43 publications
12
124
3
2
Order By: Relevance
“…In their study, Spadaro et al found no statistically significant differences between survivor and non-survivor patient groups in terms of sP-Selectin level in 31 patients followed up with mechanical ventilation [ 20 ]. Unlike this study, Vasiliou et al found the sP-Selectin level to be higher in non-survivor critically ill patients than in the survivor patient population [ 21 ].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In their study, Spadaro et al found no statistically significant differences between survivor and non-survivor patient groups in terms of sP-Selectin level in 31 patients followed up with mechanical ventilation [ 20 ]. Unlike this study, Vasiliou et al found the sP-Selectin level to be higher in non-survivor critically ill patients than in the survivor patient population [ 21 ].…”
Section: Discussioncontrasting
confidence: 75%
“…In a study conducted by Goshua et al, the levels of markers that play a role in endothelial cell and platelet activation in COVID-19 infection were examined, and the sP-Selectin level was detected to be higher in patients treated in the intensive care unit compared to patients who did not require intensive care [ 18 ]. More recently, other studies have examined the level of sP-Selectin in severe and non-severe COVID-19 patient groups as well as the sP-Selectin levels and clinical diagnostic values in critically ill patients in survivor and non-survivor groups [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a threshold of 423% of VWF (normal values: 50–150%) offered an optimal sensitivity–specificity balance [ 114 ]. Both Vassiliou et al and von Meijenfeldt et al confirmed this observation by reporting from cohorts of, respectively, 38 ICU and 102 mixed-severity COVID-19 patients, a significantly higher level of VWF factor at admission in non-survivors than in survivors [ 95 , 115 ].…”
Section: Covid-19 Is An Endothelial Diseasementioning
confidence: 93%
“…In patients on mechanical ventilation, angiopoietin-2 correlated inversely with pulmonary compliance, a measure of the lung's ability to stretch and expand [ 94 ]. Another group determined angiopoietin-2 levels on ICU admission in 38 COVID-19 patients, most of whom were mechanically ventilated [ 95 ]. Angiopoietin-2 was significantly higher in non-survivors ( n = 10) and a quite similar cut-off of 4.0 ng/mL predicted ICU mortality with a sensitivity of 89% and a specificity of 77%.…”
Section: Covid-19 Is An Endothelial Diseasementioning
confidence: 99%
See 1 more Smart Citation